Orde Baru Surveillance For PKI Ex-Political Prisoners In West Sumatra - Haldi Patra; Anatona; Yenny Narny (Criksetra: Jurnal Pendidikan Sejarah, 2022)
This article examines the New Order's supervision of ex-PKI political prisoners in West Sumatra. They were arrested after the G30S incident and were released in the 1970s. The purpose of this paper is to explain why the New Order supervised them and how the New Order government's supervision patterns of the ex-political prisoners in West Sumatra Province. This paper historical method. There are four steps in this method; heuristics, source criticism, interpretation, and historiography. This research shows that there are more than 40,000 political prisoners in this province. This Surveillance had carried out by various government agencies and carried out in a structured and systematic manner. The authorities held all the data of the ex-political prisoners. Thus it made it easier for the process to monitor them. The New Order could prevent the revival of the PKI and communism in Indonesia. As the governing regime, the New Order had the authority to run its programs. However, this policy affected the ex-political prisoner's lives because it the limitation that resulted from that policy.